2019
DOI: 10.1089/ars.2017.7487
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Thiosemicarbazones: Chemical Properties, Interaction with Iron Metabolism, and Resistance Development

Abstract: We want to emphasize that thiosemicarbazones are not solely removing iron from the cells/organism. In contrast, they should be considered as iron-interacting drugs influencing diverse biological pathways in a complex and multi-faceted mode of action. Consequently, in addition to the discussion of physicochemical properties (e.g., complex stability, redox activity), this review contains an overview on the diversity of cellular thiosemicarbazone targets and drug resistance mechanisms. Antioxid. Redox Signal. 00,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
177
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(182 citation statements)
references
References 190 publications
(234 reference statements)
4
177
1
Order By: Relevance
“…as co-factors in enzymes catalyzing essential steps in DNA-synthesis, as well as for cell cycle progression and cellular growth. [31][32][33][34] For example, the rate limiting step in DNA synthesis is the reduction of ribonucleotides, which is catalyzed by the iron dependent enzyme ribonucleotide reductase (RR). 35,36 Thus, selective toxicity of the studied compounds to the human uterine sarcoma cells over hepatocytes might be the result of the altered metal homeostasis of the cancerous cells.…”
Section: In Vitro Toxicity Of Q-1 and Its Mannich Base Derivatives Agmentioning
confidence: 99%
“…as co-factors in enzymes catalyzing essential steps in DNA-synthesis, as well as for cell cycle progression and cellular growth. [31][32][33][34] For example, the rate limiting step in DNA synthesis is the reduction of ribonucleotides, which is catalyzed by the iron dependent enzyme ribonucleotide reductase (RR). 35,36 Thus, selective toxicity of the studied compounds to the human uterine sarcoma cells over hepatocytes might be the result of the altered metal homeostasis of the cancerous cells.…”
Section: In Vitro Toxicity Of Q-1 and Its Mannich Base Derivatives Agmentioning
confidence: 99%
“…Whereas ClF and F 2 C target α and the α/β subunits of RNRs, respectively, hydroxyurea (HU) and triapine (3-AP; a thiosemicarbazone) ( Figure 15) target reduction of the essential Y r cofactor (83,99,100) in β2 and/or interfere with cofactor assembly and/or its repair if the essential Y r gets reduced (Figure 1c). HU is used clinically, predominantly in combination with other therapeutics (65), although recent studies have suggested that the RNR is not a key target of its cytotoxicity (99,101,102).…”
Section: Biosynthesis and Repair Of The Essential Diferric-y R Cofactmentioning
confidence: 99%
“…[ 13,14 ] Especially, copper complexes of thiosemicarbazone ligands present a variety of biological activities. [ 15,16 ] Another sulfur and nitrogen containing ligand is thiadiazole which known with their efficient application in agricultural, pharmaceutical, and materials chemistry. [ 17 ] Hybridization of the two ligands thiosemicarbazone and 1,3,4‐thiadiazole will afford tridentate ligand rich with nitrogen and sulfur atoms (Figure 1).…”
Section: Introductionmentioning
confidence: 99%